Estudios palinológicos en la subfamilia Asteroideae (Compositae) en el Sureste de la Peninsula Ibérica - Blanca, Gabriel; Salinas, Mari?a Jacoba; Di?az de La Guardia, Consuelo; Romero Garci?a , Ana Teresa (Acta Botanica Malacitana, 1991)
.